All Days 1991
DOI: 10.2118/21044-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rock Properties of Berea Sandstone, Baker Dolomite, and Indiana Limestone

Abstract: A complete understanding of the various rock properties is essential in determining the rockfluid interactions that take place during coreflood experiments. Although Berea sandstone, Baker dolomite and Indiana limestone have been used by the petroleum industry as reference materials, very few data have been reported in the literature regarding their basic rock properties. This paper contains petrographic and petrophysical data for these rock types. Twelve representative samples were selected to study the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(79 citation statements)
references
References 11 publications
3
72
0
1
Order By: Relevance
“…However, Churcher et al (1991) reported that Indiana limestone showed large variations in both porosity (12.1 to 21.1%) and permeability (4 to 57 mD) for the three tested samples. The two Baker dolomite samples, other than showing porosity difference, appeared to have thin layers of organic acids absorbed on the rock surfaces.…”
Section: Task 1 Appendixmentioning
confidence: 86%
See 2 more Smart Citations
“…However, Churcher et al (1991) reported that Indiana limestone showed large variations in both porosity (12.1 to 21.1%) and permeability (4 to 57 mD) for the three tested samples. The two Baker dolomite samples, other than showing porosity difference, appeared to have thin layers of organic acids absorbed on the rock surfaces.…”
Section: Task 1 Appendixmentioning
confidence: 86%
“…Very strongly water-wet rocks would have an index of unity. Churcher et al (1991) obtained comparable values of Amott Index to water and recommended extraction with a chloroform/methanol mixture for Baker dolomite samples to obtain uniform wetting before using them in flow experiments but did not test this recommendation.…”
Section: Task 1 Appendixmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 2.22 represents the total single-collector contact efficiency, and the magnitude of individual collision mechanisms (diffusion, interception and sedimentation), calculated for the silica particles used in this study, with particle density of 2.2 g/cm 3 , average grain size for Berea sandstone of 150 µm (Churcher et al, 1991) with porosity of 21%, fluid velocity of 1.5×10…”
Section: Pvmentioning
confidence: 99%
“…It is well understood that smaller grain size corresponds to smaller pore size for certain types of grain packing. For the Berea sandstone used in this study, an average grain size of 150 µm was assumed, based on Churcher et al (1991). Considering the silica particles of 2 and 5 µm, the ratio of ( ⁄ ) would be 0.013 and 0.033, respectively.…”
Section: Pvmentioning
confidence: 99%